Prototipe Sistem Monitoring Cuaca dan Peringatan Dini Hujan Berbasis Internet Of Things - Sholichin, Achmad; Susanto, Rudi; Burchim, Nurchim (LPPM STIKI MALANG, 2025)
The condition of the air at a certain time and at a certain location over a short period of time is called weather. The term